2011
DOI: 10.1111/j.1526-4637.2010.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Program in Pain Medicine for Medical Students: Integrating Core Curriculum Knowledge with Emotional and Reflective Development

Abstract: Objective Improvements in clinical pain care have not matched advances in scientific knowledge, and innovations in medical education are needed. Several streams of evidence indicate that pain education needs to address both the affective and cognitive dimensions of pain. Our aim was to design and deliver a new course in pain establishing foundation-level knowledge while comprehensively addressing the emotional development needs in this area. Setting 118 first year medical students at Johns Hopkins School of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 31 publications
0
92
0
6
Order By: Relevance
“…Training providers in empathy, a positive aspect of pain care cited in this study, may be especially helpful in CNCP care [42,43]. Novel approaches to training providers and medical students in shared decision making and affective skills improves provider satisfaction, relationships, and interest in caring for patients with pain [44,45]. Providers described feeling rewarded when they were able to alleviate suffering and provide comfort to patients, and see them regain functionality and have improved well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Training providers in empathy, a positive aspect of pain care cited in this study, may be especially helpful in CNCP care [42,43]. Novel approaches to training providers and medical students in shared decision making and affective skills improves provider satisfaction, relationships, and interest in caring for patients with pain [44,45]. Providers described feeling rewarded when they were able to alleviate suffering and provide comfort to patients, and see them regain functionality and have improved well-being.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently proposed enriched medical student pain curricula are often limited to a short interval, concentrated intersession or web-based content. 22,29,36 Mezei and Murinson 21 reported an extensive survey of all pain content taught in U.S. medical schools and found a median of just 7 sessions with a range of 1 to 28 and found that only 4% of medical schools have integrated pain material within case-based clinical teaching settings. The British Pain Society in 2009 and Briggs et al 7 have reported 13 hours of median pain curriculum in UK medical school curricula.…”
mentioning
confidence: 99%
“…These include online interactive modules, seminars and didactic teaching over a course of days or weeks, small group teaching, interactive conference series, inter-professional discussions, and use of standardized patients; application of these techniques has yielded mixed results. [36][37][38][39] One undergraduate medical education program in the US found that the integration of elements to strengthen emotional skills is an effective educational approach when teaching students about pain. 37 The investigators in this study reported that learners who used personal, reflective portfolios to build awareness of the affective dimensions of pain demonstrated attainment of foundation knowledge, robust engagement in tasks addressing emotional development, and high levels of learner satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] One undergraduate medical education program in the US found that the integration of elements to strengthen emotional skills is an effective educational approach when teaching students about pain. 37 The investigators in this study reported that learners who used personal, reflective portfolios to build awareness of the affective dimensions of pain demonstrated attainment of foundation knowledge, robust engagement in tasks addressing emotional development, and high levels of learner satisfaction. One internal medicine program in the US used a combination of interactive sessions, didactic teaching, provision of pocket reference cards, and emailing of clinical vignettes in their training program.…”
Section: Discussionmentioning
confidence: 99%